Exploding fashion : making, unmaking, and remaking twentieth-century fashion - O'Neill, Alistair ([Tielt, Belgium] : Lannoo, 2021)
Exploding Fashion' examines the impact of innovative pattern-cutting in several key examples of 20th century fashion design. With over 200 illustrations, it 'explodes' designs by 6 game-changing fashion designers from the world's leading fashion houses, and reverse engineers them in order to understand how they work. Written by a curator and professor at Central Saint Martins, London's premier college of art and design, this is the first comprehensive exploration of how a traditional design process can enter into a dialogue with new concepts, illuminating haute couture and pret-a-porter methods for a visually-driven digital age.
Wilcox, Claire ; Teissier, Myriam ; Vionnet, Madeleine ; Bolton, Andrew ; James, Charles ; Arzalluz, Miren ; Belloir, Véronique ; Balenciaga, Christobal ; Steele, Valerie ; Halston ; Nii, Rie ; Comme des Garcons
Unprecedented insight into the role of innovative pattern-cutting in contemporary fashion design Exploding Fashion unpacks the role of innovative pattern-cutting in key examples of 20th-century design. This book 'explodes' key dress designs by five game-changing fashion designers held in the world's leading dress collections, and reverse-engineers them to understand how they were made and once moved on the body. It brings traditional ways of making into dialogue with new ways of visualising, illuminating haute couture and prêt-a-porter methods for a visually-driven, digital age. (provided by publisher)
Cover title.
boek